Labor market imperfections, markups and productivity in multinationals and exporters - Sabien Dobbelaere; Kozo Kiyota (Tinbergen Institute, 2017)
This paper examines the links between the internationalization mode of firms and market imperfections in product and labor markets. We develop a framework for modelling heterogeneity across firms in terms of (i) product market power (price-cost markups), (ii) labor market imperfections (workers' bargaining power during worker-firm negotiations or firm's degree of wage-setting power) and (iii) revenue productivity. We apply this framework to analyze whether the pricing behavior of firms in product and labor markets differs across firms that engage in different forms of internationalization. Engagement in international activities is found to matter for determining not only the type of imperfections in product and labor markets but also the degree of imperfections. Clear differences in behavior between firms that serve the foreign market either through exporting or through FDI are observed. Being an exporter introduces allocative inefficiencies in product as well as labor markets as we find export status to be positively correlated with both product market power (markups) and market power consolidated on the labor supply side (workers' bargaining power). But exporting firms where search frictions are inducing wages to vary with revenue are less able to exploit wage-setting power. Firms with foreign subsidiaries, on the other hand, seem to reduce price distortions in product and labor markets. In addition, we observe heterogeneous returns to being an exporter/MNE within an industry and also discern cross-industry differences.
Keywords: C23; D24; F14; F16; J50; L13; 330; Rent sharing; monopsony; price-cost mark-ups; productivity; exporting; multinational firms; panel data